2002
DOI: 10.1021/ic020179+
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Trinuclear and Chain of Cyclic Trinuclear Copper(II) Complexes Containing a Pyramidal Cu3O(H) Core. Crystal Structures and Magnetic Properties of [Cu33-OH)(aaat)3(H2O)3](NO3)2·H2O [aaat = 3-Acetylamino-5-amino-1,2,4-triazolate] and {[Cu33-OH)(aat)33-SO4)]·6H2O}n [aat = 3-Acetylamino-1,2,4-triazolate]: New Cases of

Abstract: New copper(II) complexes of the cyclic trinuclear type with 1,2,4-triazole ligands, [Cu(3)(mu(3)-OH)(aaat)(3)(H(2)O)(3)](NO(3))(2).H(2)O [Haaat = 3-acetylamino-5-amino-1,2,4-triazole] (1) and ([Cu(3)(mu(3)-OH)(aat)(3)(mu(3)-SO(4))].6H(2)O)(n) [Haat = 3-acetylamino-1,2,4-triazole] (2), have been prepared and characterized by X-ray crystallography and magnetic measurements. Compound 1, the first reported with the ligand (H)aaat, consists of discrete trinuclear cations, associated NO(3)(-) anions and lattice wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(87 citation statements)
references
References 67 publications
2
85
0
Order By: Relevance
“…[30,31] The second model accounts for antisymmetric exchange [Equation (5)]. (5) The symmetry rules reveal that only the z component of the parameter vector will apply so that we are left with a single antisymmetric exchange parameter d z . The net effect of the antisymmetric exchange is a kind of ZFS (different from that produced by the asymmetric exchange) and a marked drop in g x ϽϽ 2.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[30,31] The second model accounts for antisymmetric exchange [Equation (5)]. (5) The symmetry rules reveal that only the z component of the parameter vector will apply so that we are left with a single antisymmetric exchange parameter d z . The net effect of the antisymmetric exchange is a kind of ZFS (different from that produced by the asymmetric exchange) and a marked drop in g x ϽϽ 2.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…In the literature we can find examples of these trinuclear complexes where the copper centers are often bridged by hydroxy groups or nitrogen heterocycles. [4][5][6] If we have in mind trinuclear nickel(II) complexes, we can find in the literature linear ones, for example, linear trinuclear nickel(II) complex with thiocyanato and pyridazine bridges have been reported by Cano et al [7] [{Ni(dien)} 2 (µ-ox){µ-Ni(CN) 4 }] can serve as an example of a trinuclear complex with oxalato as well as cyano bridges, but from a magnetic point of view, the compound can be treated as a dimer. [8] More interesting are azido-bridged trinuclear triangular complexes [{Ni(tet)} 3 (µ-N 3 ) 3 ](PF 6 ) 3 and [{Ni(tet)} 3 (µ-N 3 ) 3 ](ClO 4 ) 3 , tet = triethylenetetraamine with antiferromagnetic exchange interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the smaller value of the wavelength of the band corresponding to the transition resembles a geometry of the complex between tetrahedral and square planar. Ferrer et al [37] reported copper(II) complexes derived from 1,2,4-triazole ligands contain a pyramidal structure formed by the N,N-bridging triazolato groups. The copper atoms are five-coordinate with a distorted squarepyramidal geometry.…”
Section: Copper(ii) Spectrummentioning
confidence: 99%
“…3 Besides, the complexes with different nuclearity have been obtained depending on variables such as the co-ligand, anion and the metal-ligand ratio. 4,[21][22][23] For example, using a bitriazole ligand 1- 22 While using 1-(4-hydroxyphenyl)-1,3,4-triazole (L) and copper(II) chloride in EtOH solution, at only Cu∶L molar ratio of 5∶1, two crystalline complexes [Cu 6 (µ-Cl)(µ 3 -OH) 2 -(µ-L) 6 Cl 9 (H 2 O) 3 ]•3H 2 O and [Cu(µ-L)(µ-OH)(H 2 O) 2 ]Cl could be formed. 23 To date, only a limited number of complexes with 1-substituted-1,3,4-triazole have been described, and only a few crystal structures are known.…”
Section: Introductionmentioning
confidence: 99%